Effect of elevated temperature on concrete - Ng, Kok Keong (2009)
The need to acquire knowledge of the effect of temperature on concrete has been intensified in the recent years. This is due to the increased application of concrete in various high temperature environments. The primary aim of the project is to investigate the effect of elevated temperature on the compressive strength and load-deformation properties of concrete under no-load condition. In this project, test specimens of nominal concrete strength 37MPa and 88MPa were subjected to temperatures ranging from 100 to 500°C in increments of 100°C. Temperature gradient profiles of concrete subjected to temperature ranging from 100 to 700°C were also studied in this project.